Double-Row Arthroscopic Rotator Cuff Repair Is More Cost-Effective Than Single-Row Repair. (18th October 2017) - Huang, Adrian L.; Thavorn, Kednapa; van Katwyk, Sasha; MacDonald, Peter; Lapner, Peter
Abstract : Background: The optimal technique for arthroscopic rotator cuff repair is controversial, and both single and double-row techniques are commonly used. In the current era of increasing costs, health-care delivery models are focusing on the value of care. In this study, we compared the cost-effectiveness of single-row and double-row reconstructions in patients undergoing arthroscopic rotator cuff repair. Methods: A cost-utility analysis was performed from the perspective of a publicly funded health-care system. Health-care costs, probabilities, and utility values were derived from the published literature. Efficacy data were obtained from a previous randomized controlled trial comparing the effect of single-row (n = 48) or double-row (n = 42) reconstruction among 90 surgical patients. Unit cost data were obtained from a hospital database and the Ontario Schedule of Benefits and Fees. Results are presented as an incremental cost per quality-adjusted life year (QALY) gained. All costs are presented in 2015 Canadian dollars. A series of 1-way and probabilistic sensitivity analyses were performed. Results: Double-row fixation was more costly (2, 134.41 compared with 1, 654.76) but was more effective than the single-row method (4.073 compared with 4.055 QALYs). An incremental cost-effectiveness ratio (ICER) was estimated to be 26, 666.75 per QALY gained for double-row relative to single-row fixation. A subgroup analysis demonstrated that patients with larger rotator cuff tears (≥3 cm) had a lower ICER, suggesting that double-row fixation may be more cost-effective for larger tears. Conclusions: Based on the willingness-to-pay threshold of 50, 000 per QALY gained, double-row fixation was found to be more cost-effective than single-row. Furthermore, a double-row reconstruction was found to be more economically attractive for larger rotator cuff tears (≥3 cm). Level of Evidence: Economic and Decision AnalysisLevel IV . See Instructions for Authors for a complete description of levels of evidence.